CADRE ROTATION AND CAMPAIGN MOBILIZATION IN CHINA'S ANTICORRUPTION ENFORCEMENT. (27th February 2017) - Zeng, Qingjie
Abstract: In authoritarian regimes, anticorruption measures are fundamentally mechanisms of controlling agents at various levels. To do this, the principal can either rely on routine bureaucratic management or resort to ad hoc, intense mobilization to discipline its agents. Using China as a case study, this article explores which mode of top-down control exerts greater influence on the pattern of anticorruption enforcement. We focus on the cadre rotation system as an example of routine management techniques and examine its effects on provincial level enforcement. We also investigate how provinces respond to the central government's periodic call to intensify anticorruption efforts. Based on provincial enforcement data from 1998 to 2013, our analysis finds that the proportion of rotated officials has little impact on enforcement outcomes. Rather, the vigor of enforcement in the provinces responds strongly to national policy priorities, suggesting a highly centralized disciplinary system. Moreover, provinces of greater political importance are under more central pressure to conform. The findings challenge the often-made argument that stable institutions are effective in fostering top-down control in authoritarian regimes, and suggest that campaign mobilization continues to be an essential instrument at the dictator's disposal.